(3ehShYI WQGFa GdeYdheGJs - (3MSf, NejSs ((3GdLjRI, eUQ (B:s (3gHI Gdfjd GdYQHjI ddfTQ hGdJhRjY,s, 2006)
(3jJfGhd GdcJGH eYdheGJ eKjQI hYLjHI hTNUjGJ JGQjNjI HGQRI hWQGFa COHjI hYdejI(B.s
Keywords: (3OhGFQ GdeYGQa GdYQHjIs